THE INFLUENCE OF SOCIAL MEDIA, SEARCH ENGINE OPTIMIZATION, CONTENT STRATEGY, AND FINANCIAL REPORT QUALITY ON BUSINESS GROWTH - Darmayanti, Novi; Manaf Dientrimei, Abdul; Ali Wafa, Moh; Imama Nurun Najjah, Fella; binti Jamil, Amirah (Prodi Akuntansi FEB UNITOMO, 2024)
ABSTRACT This study aims to examine the influence of social media, search engine optimization, content strategy, and financial report quality on business growth (A Study on Micro-Enterprises in Lamongan Regency). This research was conducted in Lamongan, involving 99 micro-enterprise owners throughout Lamongan Regency as respondents. This quantitative study employs multiple linear regression. The technique is processed with SmartPLS to analyze several hypotheses. The inter-correlation model between the four variables in this study reveals that social media, content strategy, and financial report quality have a significant correlation with business growth; however, the search engine optimization variable does not have a significant correlation with business growth. Keywords: Social Media, Search Engine Optimization, Content Strategy, Financial Report Quality.